A highly tough and ultralow friction resin nanocomposite with crosslinkable polymer-encapsulated nanoparticles. (15th September 2020) - Gong, Hanjun; Song, Yan; Li, Guo Liang; Xie, Guoxin; Luo, Jianbin
Abstract: A resin nanocomposite embedded by encapsulated nanoparticles with exceptional mechanical and lubrication properties is reported. The functional encapsulated nanoparticles, synthesized by miniemulsion co -polymerization of methyl methacrylate with n -butyl acrylate, styrene and glycidyl methacrylate, had tunable glass transition temperatures and surface reactive glycidyl groups. The as-synthesized nanoparticles with controlled size, shell component and surface function, impacted a nanocomposite with the high toughness and strength as well as ultralow friction properties by their covalent crosslinking with the matrix and the formation of thin boundary lubricant film. Remarkably, the optimal toughness and strength of the nanocomposite with encapsulated nanoparticles achieved 3.8 and 1.5 times those of the counterpart with encapsulated microparticles, respectively. The nanocomposite incorporated with as-synthesized nanoparticles exhibited an ultralow coefficient of friction (COF) and a wear rate of 0.027 and 8.0 × 10 −7 mm 3 /Nm, which were only 3.9% and 0.6% those of the matrix, respectively. The developed robust mechanical and ultralow friction resin nanocomposite from crosslinkable and flexible polymer-encapsulated nanoparticles is highly expected for engineering applications. Graphical abstract: Image 1